Impact of GDP and Inflation on Stock Market in India: A Case Study of BSE Index - Kushwaha, Satyendra; Kafle, Sarad Chandra; Khanal, Baburam (BMC Journal of Scientific Research, 2023)
Stock market is affected by various factors. Among them, gross domestic product and inflation are the major variables. This research paper focuses how GDP and inflation affect the Indian stock market. Objective of this study is to examine the association between real GDP, inflation, and the performance of the Indian stock market. This research studies the impact of GDP and Inflation on volatility between the Bombay Stock Exchange (BSE) and macroeconomic variables. The analysis uses a multiple regression equation model to examine how these factors interact. The data collected consists of annual records of Real GDP and the inflation rate spanning from 1980 to 2021. The result shows that there is the strong positive correlation between GDP and BSE index. Similarly, there is the moderate negative correlation between Inflation and BSE index. The regression model provides the very strong impact of independent variables on the BSE index where independent variables are explaining 88.5% variation in BSE Index. Also, BSE increases 17.08% with a one percentage point GDP growth, where as one percentage increase in Inflation makes 2.17% decrease in BSE. The study found the microeconomic variable GDP and Inflation used in regression analysis are good explanatory variables. The regression model developed in this study is important in explaining the relationship between the dependent and independent variables. Stock market performance is typically shaped by various macroeconomic factors, including interest rates, remittances, foreign direct investment, per capita income, and dividends. However, the current research only employs two explanatory variables to analyze stock prices. Therefore, there is an opportunity for further investigation to elucidate how these additional explanatory variables impact stock prices. Findings of the research help the concerned stakeholders for making policy and aware them in the investment plans.